2013
DOI: 10.1161/circulationaha.113.002332
|View full text |Cite
|
Sign up to set email alerts
|

Management and Outcomes of Major Bleeding During Treatment With Dabigatran or Warfarin

Abstract: Most vitamin K antagonists have a long half-life (acenocoumarol, 10 h; warfarin, 36-48 h; phenprocoumon, 120-150 h), Background-The aim of this study was to compare the management and prognosis of major bleeding in patients treated with dabigatran or warfarin. Methods and Results-Two independent investigators reviewed bleeding reports from 1034 individuals with 1121 major bleeds enrolled in 5 phase III trials comparing dabigatran with warfarin in 27 419 patients treated for 6 to 36 months. Patients with major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
139
1
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(156 citation statements)
references
References 37 publications
7
139
1
9
Order By: Relevance
“…The INR in RHD patients versus patients with other cardiac condition was nearly the same 2-3. This is in agreement with study was performed by Schafer et al (2007) andAmerican Heart Association, (2014), who reported that; the target INR ranges of 2.0 to 3.0 or 2.5 to 3.5 have been recommended for most indications because INR values in these ranges are associated with the best combination of thrombosis reduction and bleeding avoidance (1,5); it also agrees with Majeed etal, ( 2013) whostated thatfor patients on anticoagulants, the INR typically should be between 2.0 and 3.0 for patients with RHD; or between 3.0 and 4.0 for patients with AF;for patients on warfarin therapy, an INR recall interval not exceeding 4 weeks has traditionally been recommended; less frequent INR monitoring may be feasible in stable patients (14). In the current study, PC of patients with RHD was about 68% and in patients with valve replacement was about 52 %, so warfarin therapy is complicated by a narrow TTR and substantial interpatient variability in dose response as reported byPiccini etal, (2014); if the INR values were not within the target range, anticoagulation service asked and recorded the most appropriate reasons (4).…”
Section: Discussion:-supporting
confidence: 59%
“…The INR in RHD patients versus patients with other cardiac condition was nearly the same 2-3. This is in agreement with study was performed by Schafer et al (2007) andAmerican Heart Association, (2014), who reported that; the target INR ranges of 2.0 to 3.0 or 2.5 to 3.5 have been recommended for most indications because INR values in these ranges are associated with the best combination of thrombosis reduction and bleeding avoidance (1,5); it also agrees with Majeed etal, ( 2013) whostated thatfor patients on anticoagulants, the INR typically should be between 2.0 and 3.0 for patients with RHD; or between 3.0 and 4.0 for patients with AF;for patients on warfarin therapy, an INR recall interval not exceeding 4 weeks has traditionally been recommended; less frequent INR monitoring may be feasible in stable patients (14). In the current study, PC of patients with RHD was about 68% and in patients with valve replacement was about 52 %, so warfarin therapy is complicated by a narrow TTR and substantial interpatient variability in dose response as reported byPiccini etal, (2014); if the INR values were not within the target range, anticoagulation service asked and recorded the most appropriate reasons (4).…”
Section: Discussion:-supporting
confidence: 59%
“…Sebbene l'esperienza clinica nell'utilizzo dell'emodialisi (emofiltrazione) per l'eliminazione di dabigatran sia limitata, in particolare, nelle situazioni di emergenza, essa risulta essere un'opzione da considerare poiché consente di ridurre le concentrazioni plasmatiche di dabigatran. Va sottolineato che, in un contesto di emergenza l'accesso alla procedura emodialitica potrebbe essere limitato [20][21][22][23]. Con la disponibilità di idarucizumab, è emerso che si eviterebbero i trattamenti con emodialisi in tutti i tipi di emorragie (intracranici, gastrointestinali, e altre) e negli interventi chirurgici di emergenza.…”
Section: Tabella V Risultati Dell'analisi Di Budget Impact Per Announclassified
“…36 These data might suggest that major bleedings associated with the treatment with TSOACs, in particular dabigatran, have a more favorable outcome than bleeding on warfarin, even if a specific antidote is not available yet.…”
mentioning
confidence: 99%